PENGARUH PROFITABILITAS, KEPEMILIKAN MANAJERIAL, DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN HUTANG - Sonya Enda Natasha S. Pandia; Suriani Ginting (Jurnal Ilmu Manajemen METHONOMIX, 2020)
This research aims to determine and analyze the influence of profitability, managerial ownership, and firm size on debt policy. The populations in this research were 177 companies. The sampling method in this research was purposive sampling and obtained 19 sample companies. Analysis of data method used multiple linear regression analysis. The result of the analysis shows that simultaneously profitability, managerial ownership, and firm size have a significant effect on debt policy. Partially, profitability and managerial ownership have a significant and negative effect on debt policy. While firm size has not significant on debt policy.